Pengaruh Label Halal Terhadap Keputusan Pembelian Produk Kosmetik Wardah Outlet Cantik Mart Plered Purwakarta - Herdi, Rahmawati; Sucipto, Moch Cahyo; Sopian, Ahmad Ali (EKSISBANK (Ekonomi Syariah dan Bisnis Perbankan), 2025)
Cosmetics are one of the products offered to meet consumers' secondary needs and desires to look more beautiful and attractive. Since the majority of the population in Indonesia is Muslim, the certainty of a product's halal status is an important consideration. The development of halal cosmetics in Indonesia has seen significant growth. This is marked by the emergence of various cosmetic companies with different brands. One of the most well-known cosmetic brands in society is Wardah. The purpose of this study is to determine the influence of halal labeling on purchasing decisions for Wardah cosmetic products at the Cantik Mart Plered Purwakarta outlet, as well as to measure the extent of this influence on purchasing decisions. This research uses a quantitative descriptive method with a population of 112 respondents and a sample using the purposive sampling technique calculated using the Slovin formula with a 5% error rate, resulting in a sample size of 87 respondents. The results of this study can be concluded that the Halal Label has an influence on consumers' decisions to purchase cosmetics at the Wardah Cantik Mart Plered Purwakarta outlet. This is evidenced by the calculated t-value being greater than the table t-value (10.059 > 1.98827) with a significance level less than 0.05 (0.000 < 0.05). Based on these data, it can be stated that the Halal Label has a significant influence. The extent of the Halal Label's influence on purchasing decisions can be seen from the T-test results, which yielded an R-square value of 0.571. Thus, the results of this study indicate that the Halal Label influences purchasing decisions by 57.1%, while the remaining 42.9% is influenced by variables outside the scope of this study.